The Role of Literacy in Increasing Children's Reading Interest in Early Childhood - Choiriyah, Choiriyah; Widiati, Debora Pujo; Emiliana, Widiarti (Indonesian Journal of Early Childhood Education Studies, 2023)
Children's ability to understand reading information still needs to be guided and directed. Children's ability to think, increase their vocabulary, and develop a literacy culture still needs to improve in optimizing children's brain performance. This study aimed to explore the role of literacy in increasing early childhood interest in reading. This study uses a qualitative methodology with data collection methods using observation and interviews. The subjects in this study were five students' parents as the primary informants who were randomly selected. The data analysis technique uses the Miles and Huberman approach, and the validity of the data uses source triangulation. The findings show that literacy skills are very close to children's daily lives and can be built from infancy. They start when the child can recognize pictures, writing, and numbers to assemble letters into words. Children's reading ability can be influenced by the surrounding environment, namely the family, both parents and teachers. The role of parents can be reading storybooks to children, singing, and reciting nursery rhymes, which is a valuable way of developing literacy in early childhood. So far, learning to read in early childhood is limited to using reading books to provide letter recognition opportunities. Here, the role of literacy through reading books will give a meaningful impression to children learning to read that many people have never known so that it becomes a new thing. The advantage of the results of this study is that the child's reading level has more insight to increase knowledge and a way of thinking to apply much vocabulary.